Effects of triiodothyronine hormone and iodine supplements on the performance of broilers in cold environment - Seven, P. Tatli; Seven, I. (My University, 2009)
In this study, 150, one-day-old, broiler chicks (Ross 308) were used. Chicks were randomized into 1 control and 4 experimental groups each containing 30 birds and each group was divided into one main and two replicate groups. Group I (control) was fed basal diet, group II was fed with basal diet supplemented with 1 mg/kg T3, group III was fed with basal diet supplemented with 1.5 mg/kg T3, group IV was fed with basal diet supplemented with 2 mg/kg iodine as calcium iodate, group V was fed with basal diet supplemented 3mg/kg iodine. Chicks in control group gained significantly less (P<0.05) in comparison to dietary iodine groups (Group IV & V) at 40 days age. Iodine supplementation (Group IV & V) increased body weight gain significantly over that of control group during 15-40 days age. FCR of chicks in group III (1.5 mg/kg T3 diet) was significantly (P<0.05) better than that of control during 29-40 days age. There was no significant difference in FCR of broiler chicks among groups III, IV and V and between control group and group II. The ash retention in control chick was significantly lower than that of group V (P<0.01). The protein retentions of iodine groups (Group IV & V) were highest than other groups (P<0.01). Relative weights of heart and thyroid were significantly different among the groups (P<0.01).
Keywords: Aves